Use of the Rockwood Clinical Frailty Scale in patients with advanced hepatopancreaticobiliary malignancies. Issue 9 (2nd September 2022) - Shah, Dinakshi; Kapacee, Zainul Abedin; Lamarca, Angela; Hubner, Richard A; Valle, Juan W; McNamara, Mairéad G
ABSTRACT: Background: Co-existing frailty in older patients with hepatopancreaticobiliary (HPB) malignancies is common. This study assessed the relationship between the Rockwood Clinical Frailty scale (CFS) and systemic anti-cancer therapy dose intensity (SACT-DI) and overall survival (OS) in patients with advanced HPB malignancies. Research design and methods: CFS was assessed prospectively for consecutive patients with newly diagnosed advanced HPB malignancy (The Christie; Sep-2019 to June-2020). Mann-Whitney U test assessed association between CFS, ECOG Performance Status (ECOG PS), and SACT-DI and Spearman's rank assessed the association between ECOG PS, age, and frailty. Survival analysis was performed using Kaplan-Meier and Cox regression. Results: Two hundred patients met inclusion criteria. SACT-DI was higher in Group-1 (not frail) (CFS 1–3)(median = 61%) than Group-2 (vulnerable/mildly frail) (CFS 4–5)(median = 25.1%), p < 0.001. Median OS was shorter in frail and pre-frail patients (HR 2.3(95%CI 1.8–2.9), p < 0.001. On multivariable analysis, both CFS (HR 1.5-(95%CI 1.2–1.9), p = 0.002) and ECOG PS (HR 1.9 (95%CI 1.6–2.3), p < 0.001) were independent prognostic factors for OS. Conclusion: Frailty assessments, in addition to ECOG PS, may identify patients that will benefit from systemic therapy and are both independent prognostic factors for OS.